Immunomodulatory Effects of Tryptophan Metabolism in the Glioma Tumor Microenvironment - Xu, Yang; Zhang, Huikai; Sun, Qian; Geng, Rongxin; Yuan, Fanen; Liu, Baohui; Chen, Qianxue (Frontiers in Immunology, 2021)
Gliomas are the most common primary malignant tumor in adults’ central nervous system. While current research on glioma treatment is advancing rapidly, there is still no breakthrough in long-term treatment. Abnormalities in the immune regulatory mechanism in the tumor microenvironment are essential to tumor cell survival. The alteration of amino acid metabolism is considered a sign of tumor cells, significantly impacting tumor cells and immune regulation mechanisms in the tumor microenvironment. Despite the fact that the metabolism of tryptophan in tumors is currently discussed in the literature, we herein focused on reviewing the immune regulation of tryptophan metabolism in the tumor microenvironment of gliomas and analyzed possible immune targets. The objective is to identify potential targets for the treatment of glioma and improve the efficiency of immunotherapy.